Screen Time in Children of Central Nepal: A Parent Reported Cross-sectional Study during COVID-19 Pandemic - Radha Bhurtel; Ram Prasad Pokhrel; Sumitra Sharma (Journal of Lumbini Medical College, 2022)
Introduction: The insurgence of COVID-19 has affected many aspects of human life and its repercussions on the life of children cannot be undermined. In addition to the serious impact on health and food insecurity, lack of recreational activities, school closure and switch to online learning have pushed children to excessive screen exposure. This study aimed to assess the duration of screen time and parental perspective towards screen viewing in children during the pandemic. Methods: A community-based descriptive cross-sectional study was carried out in Bharatpur Metropolitan City. A total of 384 parents were included purposively. A semi-structured questionnaire was used to interview the parents during the pandemic for one month. During the data collection, appropriate universal precautions for COVID-19 were taken. Results: The median duration of screen exposure was two hours (30 minutes to 9 hours). Most (65%) of the parents stated that their children spent more time on screen compared to pre-COVID-19 times. The majority (82%) of the parents were worried about the possible consequences of excessive screen time. More than two-thirds (72%) of parents thought that screen exposure also has various benefits for children. Conclusion: Most of the children exceeded the duration of screen time recommended by the World Health Organization. Most of the parents were worried about the harmful effects on the health and behavior of children.